The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jbm.a.37151
|View full text |Cite
|
Sign up to set email alerts
|

Surface activation with oxygen plasma promotes osteogenesis with enhanced extracellular matrix formation in three‐dimensional microporous scaffolds

Abstract: Various types of synthetic polyesters have been developed as biomaterials for tissue engineering. These materials commonly possess biodegradability, biocompatibility, and formability, which are preferable properties for bone regeneration. The major challenge of using synthetic polyesters is the result of low cell affinity due to their hydrophobic nature, which hinders efficient cell seeding and active cell dynamics. To improve wettability, plasma treatment is widely used in industry. Here, we performed surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“… 67 In rBMSC, the consequence of the robust mRNA expression of RUNX2 may be either cytoskeletal expression/diffusion or nuclear localisation. 29 In the present study, the quantification and line investigation confirmed that the mRNA upregulation of RUNX2 by fluid flow was accompanied by a degree of nuclear localisation. Similarly, collagen formation, ALP activity and mineral deposition were found to be enhanced in the dynamic culture groups.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“… 67 In rBMSC, the consequence of the robust mRNA expression of RUNX2 may be either cytoskeletal expression/diffusion or nuclear localisation. 29 In the present study, the quantification and line investigation confirmed that the mRNA upregulation of RUNX2 by fluid flow was accompanied by a degree of nuclear localisation. Similarly, collagen formation, ALP activity and mineral deposition were found to be enhanced in the dynamic culture groups.…”
Section: Discussionsupporting
confidence: 78%
“… 68 Nevertheless, the induction of osteogenesis, particularly in terms of collagen formation and mineral deposition, by fluid flow is apparently not as robust as that achieved by the osteogenic supplements as previously tested in a study of osteogenic differentiation of rBMSC on LTMC scaffolds. 29 This could be attributable to the characteristics of each component of the common osteogenic supplement (i.e. dexamethasone, β-glycerophosphate and ascorbic acid).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations